A New Challenge for Universities: Assessing the Quality of Management of the Undergraduate Dissertations - Jesús Vera Giménez; Elena Briones Pérez (FahrenHouse, 2016)
Introduction: The Spanish university has recently faced the challenge of managing the preparation of students for developing their Undergraduate Dissertation (UD). This new requirement imposed by the legislation for obtaining graduate degree has meant the involvement of almost all the university teachers and students ending their Degree. This article raises the convenience to monitor the quality management processes of UD to assess their suitability form the perspective of students. Method: A survey made to evaluate the quality of the management of UD was evaluated by 118 academics. From the contributions of evaluators the survey was rebuilt as it is offered in the Annex. During the years 2012 to 2014 the survey was conducted and answered by 1422 students. Results and discussion: A suitable reliability of the five scales included in the survey was observed. It is essential improvements in the best predictors of student satisfaction: tutor training, establishing more efficient and transparent criteria for the panels to assess the UD, to improve the quality of information provided to students to face the UD, adjust the allocation of credits to adjust the degree of dedication that students invest in their development.